1997
DOI: 10.1190/1.1444273
|View full text |Cite
|
Sign up to set email alerts
|

Application of perfectly matched layers to the transient modeling of subsurface EM problems

Abstract: magnetic field for a pulsed horizontal magnetic dipole embedded in a resistive whole space. The conductivity of the whole space is 0.001 S/m, the relative electric permittivity and relative magnetic permeability are equal to one. The x-directed dipole moment varies in time as where c ϭ 2f max and f max is 300 kHz. These model parameters are chosen to simulate a radio imaging method (RIM)-type transmitter with one or more horizontal wire loops lowered down the boreholes for transmission, reception, or both, ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…Rappapport (1995) proved that the PML is equivalent to anisotropic media in the absorption area. Many examples (Chew and Weedon, 1994;Chen et al, 1997) demonstrated that the absorption of the PML absorbing boundary condition is much better than exponential attenuation ABCs (Marfurt, 1984;Shin, 1995), Mur ABCs (Liao et al, 1984), and Higdon ABCs (Higdon, 1991). Chen et al (1997) and Wang and Oristaglio (2000) successfully applied PML ABCs to solve the electromagnetic wave equation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rappapport (1995) proved that the PML is equivalent to anisotropic media in the absorption area. Many examples (Chew and Weedon, 1994;Chen et al, 1997) demonstrated that the absorption of the PML absorbing boundary condition is much better than exponential attenuation ABCs (Marfurt, 1984;Shin, 1995), Mur ABCs (Liao et al, 1984), and Higdon ABCs (Higdon, 1991). Chen et al (1997) and Wang and Oristaglio (2000) successfully applied PML ABCs to solve the electromagnetic wave equation.…”
Section: Introductionmentioning
confidence: 97%
“…Many examples (Chew and Weedon, 1994;Chen et al, 1997) demonstrated that the absorption of the PML absorbing boundary condition is much better than exponential attenuation ABCs (Marfurt, 1984;Shin, 1995), Mur ABCs (Liao et al, 1984), and Higdon ABCs (Higdon, 1991). Chen et al (1997) and Wang and Oristaglio (2000) successfully applied PML ABCs to solve the electromagnetic wave equation. In recent years, the PML was widely applied in acoustic and elastic wave finite-difference forward modeling (Rappapport, 1995;Chew and Liu, 1996;Hastings et al, 1996;Komatitsch and Tromp, 1999;Collino and Tsogka, 2001;Festa and Nielsen, 2003;Basu and Chopra, 2004;Cohen and Fauqueux, 2005;Festa and Vilotte, 2005;Appelö and Kreiss, 2006;Ma and Liu, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…These modeling codes were initially written in MATLAB, but were then written to interface MATLAB with C-code in order to significantly increase the speed of the field updating loops. The codes also incorporate the perfectly matched layer (PML) absorbing boundary technique (Berenger, 1994;Fang and Wu, 1996;Chen et al, 1997), which is the most effective method known for the absorption of waves at the edges of a simulation grid at any angle of incidence. Finally, we are in the process of implementing the codes on a 16-node parallel computing cluster at Stanford, which will significantly decrease the time needed for modeling.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The source is a -oriented electric Hertzian dipole located at the grid point ( ), while the receiver is located at ( ). The excitation pulse is the first derivative of a modified Blackman-Harris pulse [34], centered at 200 MHz. The receiver is deliberately buried in the half space so that it is more sensitive to the dispersive properties of the medium.…”
Section: A Validationmentioning
confidence: 99%